Effectiveness of Recruitment Policies in Attracting and Retaining Qualified Talent in the Company - Murfat, Moh. Zulkifli; Mohamad, Mahathir; Nasir, Munawir; Murfat, Moh. Zulfachmi (Advances in Human Resource Management Research, 2025)
Purpose: This study aims to evaluate the effectiveness of recruitment policies in attracting and retaining qualified talent within organizations by assessing key factors, including the selection process, compensation packages, candidate experience, career development opportunities, and work-life balance initiatives. The research seeks to provide a comprehensive understanding of how recruitment strategies can influence both short-term hiring success and long-term employee retention. Research Design and Methodology: A qualitative systematic literature review (SLR) approach was employed to assess existing recruitment and retention practices research critically. The study synthesized findings from recent academic and industry-related sources to identify patterns, key trends, and gaps in current recruitment frameworks. By adopting a holistic review methodology, the study aims to connect theoretical insights with practical strategies for improving talent management. Findings and Discussion: The study found that effective recruitment policies extend beyond the hiring process and contribute significantly to fostering employee engagement and organizational loyalty. Transparent communication, fair selection procedures, and clear career pathways were key candidate satisfaction and long-term retention drivers. Additionally, work-life balance policies, competitive compensation, and inclusive work environments strengthened emotional attachment and commitment to the organization. These findings highlight the importance of designing recruitment policies that align with organizational values and support professional and personal growth. Implications: The study emphasizes the need for organizations to integrate recruitment strategies with holistic human resource development frameworks. The practical consequences suggest implementing comprehensive onboarding programs, flexible work arrangements, and continuous training initiatives to enhance employee loyalty and resilience. This research offers actionable insights into developing adaptive recruitment policies that enhance competitiveness and sustainability in dynamic labor markets.